Comparative analysis of conventional methods for the evaluation of wettability in shales - Sharifigaliuk, H. (Elsevier B.V., 2022)
Wettability has paramount importance in the characterization of shale reservoirs, yet its determination is quite challenging. The conventional techniques popularly applied for wettability determination of shales include contact angle, spontaneous imbibition, and floatation. However, there is no consensus as to the most appropriate method of assessing shale wettability, and which method is most suitable for a given shale sample. In this study, these techniques were employed to measure the wettability of outcrop Eagle Ford, Mancos, and Marcellus shale samples simultaneously to compare their efficacy. Sessile/Captive contact angles were measured on dry and saturated shale samples. The advancing/receding contact angles were also investigated by the drop-volume inflation/deflation method to understand wettability hysteresis. A better evaluation of shale surfacesâ wettability was attained when a water drop was gently placed on the water-saturated chips submerged in the bulk of oil and the contact angle between oil and water was measured. The contact angle and floatation methods showed relatively good agreement, perhaps because both methods relate to shale surficial affinity and mineralogy. However, the wettability of Eagle Ford and Mancos samples derived from contact angle, spontaneous imbibition, and floatation methods were not entirely similar. Only the spontaneous imbibition method was able to evaluate the mixed-wet characteristics of Marcellus shale samples properly because of the overlapped oil and brine saturation due to imbibition. The observed wettabilities are only specified for the studied outcrop samples. A novel approach somewhat like the Amott method is proposed for the quantitative assessment of wettability from spontaneous imbibition datasets, especially for mixed-wet rocks like shales. Overall, the order of reliability of the conventional techniques is spontaneous imbibition > contact angle > floatation. Â© 2021 Elsevier B.V.